You probably understand this just fine, it's just shorthand.
If y=f(x) then y(x)=f(x). But I might use y later like a variable as in
the above line just means
and probably more importantly
Is it any clearer now?
i am having trouble understanding the notation y=y(x). I understand the functional notation y=f(x).
I have been trying to study implicit functions and this notation is used quite regularly. What would be the best reference? Could someone please provide some insight?
A function f is a rule which assigns a value (dependent) to one or more values (independent).
Ex f= sin, cos, square, sqrt, etc.
y=f(x) says y is the value f assigns to x.
y alone can stand for either a dependent or independent variable.
y=y(x) says y depends on x and is a shortcut which says y is the function and the value of the function.
Sometimes shortcut can lead to confusion:
y=f(x), x=g(z), y=f(g(z)) = F(z)
y=y(x), x=x(z), y=y(x(z)) =? y(z). y in y(z) is not the same function as y in y(x). You have to keep track.
x+2y=3 defines y as a fuction of x or x as a function of y.
or, think of x and y as functions of t:
dx/dt+2dy/dt=0 and multiply through by dt:
dx+2dy=0 and solve for dx/dy or dy/dx.
or, f(x,y)=0 -> df=0 and solve for dx/dy or dy/dx
Normally, this convention comes up in the study of differential equations: that is, equations involving functions and their derivatives.
Normally, we have a function, f, defined on a domain X, and which takes values in Y, as in f: X-->Y.
Often, both X and Y are the "same kind of thing", as is the case when both equal the set of real numbers. It is then common to represent f as a subset of the plane (a GRAPH) consisting of those points in the plane:
(x,y) such that y = f(x). What is really meant by the statement "y = y(x)" is actually: "we're only interested in those points (x,y), where (x,y) = (x,f(x)) for some function f " (also, somewhat confusingly, labeling the function f, "y" as well).
The important thing to realize, is that when we say "y = y(x)" what we intend to get across is that when we DIFFERENTIATE, we are differentiating with respect to x:
For example, if we want to find the slope of the tangent line to a circle of radius 1 at the point (a,b) on the circle, we do this:
x2 + y2 = 1 is our implicit definition.
Differentiating with respect to x (and using the chain rule), we get:
. Note that .
Solving for dy/dx:
Substituting in: x = a, y = b, we get the slope is -a/b. For example, at the point (0,1), the slope of the tangent line is 0, and at the point (√2/2, √2/2) the slope of the tangent line is -1.